1999
DOI: 10.1381/096089299765552756
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy in Obese and Nonobese Patients

Abstract: LC was a safe and effective treatment for obese patients with symptomatic cholelithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 7 publications
4
11
0
Order By: Relevance
“…Gatsoulis et al 13 stated that obesity may complicate any surgical procedure but has no influence on the conversion rate, and our series supported their opinion. Acute cholecystitis, male sex, high temperature, high serum lactate dehydrogenase, thickened gallbladder wall on ultrasound, and high white blood cell count could be risk factors for a high conversion rate.…”
Section: Discussionsupporting
confidence: 84%
“…Gatsoulis et al 13 stated that obesity may complicate any surgical procedure but has no influence on the conversion rate, and our series supported their opinion. Acute cholecystitis, male sex, high temperature, high serum lactate dehydrogenase, thickened gallbladder wall on ultrasound, and high white blood cell count could be risk factors for a high conversion rate.…”
Section: Discussionsupporting
confidence: 84%
“…This must be balanced with the risks associated with cholecystectomy. Laparoscopic cholecystectomy is safe in obese patients [29][30][31]. In patients undergoing laparoscopic RYGBP, placement of the trocars is not ideal for cholecystectomy and may make it more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, the issue of laparoscopic surgery in obese patients has been rarely addressed. Because several reports have shown that laparoscopic procedures in obese patients have not been associated with higher morbidity rates in gynecology [7,10], urology [6], and for laparoscopic cholecystectomy [8,18], several experienced centers assessed the outcome of laparoscopic surgery for colorectal disease in obese patients.…”
Section: Discussionmentioning
confidence: 99%